In vitro identification and control of Pestalotiopsis longisetula fungus, pathogens strawberry crop - Teixeira, Manoel Araujo; Martins, Rúbia Marcia Siqueira; Vieira, Rosana Faria; Vildoso, Carlos Ivan Aguilar; Adami, Angélica Aparecida Vieira; Ferreira, Ana Cristina (Revista Agrogeoambiental, 2015)
Over the past seven years, pestalotiopsis has been the main strawberry disease found all over the crops located in the south of Minas Gerais State, Brazil. The leaves of the plants were severely attacked by an uncommon fungus in the regional crops, mainly in 2005 and 2006. The non-immediate identification of the microorganism resulted in catastrophic pathogen control processes performed by farmers who, eagerly trying to save their crops ended up using a series of toxic agrochemicals that had been previously purchased for the control of other types of diseases. Due to these events, the present paper aims at identifying the pathogen and put chemical as well as biological products into test that might help control the disease. Results showed that no fungicide under test in the present experiment was able to inhibit the isolate at a 100% rate, even under in vitro conditions. Pathogen identification revealed a fungi known as Pestalotiopsis longisetula.